2021
DOI: 10.2147/ijn.s317231
|View full text |Cite
|
Sign up to set email alerts
|

Structural Deformation of MTX Induced by Nanodrug Conjugation Dictate Intracellular Drug Transport and Drug Efficacy

Abstract: Background: Understanding structural interactions between the active drug and conjugated nanoparticles is critical for optimizing intracellular drug transport and for increasing nano drug efficacy. In this regard, analyzing the conformational deformation of conjugated drugs surrounding nanoparticles is essential to understand the corresponding nanodrug efficacy. Purpose: The objective of this study is to present an optimal synthesis method for efficient drug delivery through a clear structural analysis of nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Fig. 6B shows two negative minima around 208 nm and 222 nm, suggesting that all proteins adopt the helical structure, similarly (Park et al 2021). The secondary structural composition calculated by the software, CDNN revealed more than 90% of the secondary components are α-helices, which is in good agreement with the predicted structure as shown in Fig.…”
Section: Structural Characteristic Of Grim-19supporting
confidence: 80%
“…Fig. 6B shows two negative minima around 208 nm and 222 nm, suggesting that all proteins adopt the helical structure, similarly (Park et al 2021). The secondary structural composition calculated by the software, CDNN revealed more than 90% of the secondary components are α-helices, which is in good agreement with the predicted structure as shown in Fig.…”
Section: Structural Characteristic Of Grim-19supporting
confidence: 80%
“…The literature has shown that covalent conjugation of CNT-DOX in intracellular trafficking assays represents a more stable drug conjugation style in intracellular drug delivery systems [ 35 ]. In this study, intracellular drug delivery analysis showed that early endosome (EE) and LE signal intensities were analyzed in normal lung cancer cells (A549 and H446 cells) and multidrug-resistant SCLC cells (H69AR cells) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Modifications in the structural variants of MTX enhanced the anti-inflammatory drug effectiveness of human fibroblast like synovial cells (FLS) through sustained extracellular drug release and burst drug release beneath intracellular state. 69 Moreover, methotrexate (MTX) has adverse side effects such as gastrointestinal complications and hepatotoxicity leading to MTX discontinuation. Subsequently, a highpressure carbon monoxide synthesized single-walled carbon nanotubes (HiPco-SWCNTs) and carboxyl-SWCNTs combined with a small interfering RNA (siRNA) targeting NOTCH1gene are examined as drug carrier for methotrexate.…”
Section: Effective Utilization and Outcomes Of Carbon Nanotubes In Dr...mentioning
confidence: 99%